Bioaccumulation of heavy metals in some shell fishes and soil from polluted in chaktai khal of karnafully River, Chittagong - Sultana, Tania; Rahman, Mizanur; Ali, Md; Ahmed, Abu Tweb Abu (Bangladesh Journal of Zoology, 2015)
Abstract not available Bangladesh J. Zool. 43(1): 145-151, 2015